Flexibility of Marketing Strategy, Product Suitability, Consumer Responsibility, Personal Branding, Market Demand Towards the Existence of WFL Coffee Shop, Anambas Regency - Pitri, Amalia; Tibrani, Tibrani; Ismanto, Widodo (Amkop Management Accounting Review (AMAR), 2025)
The rapid growth of coffee shops in Anambas Regency has intensified competition, requiring operators to adopt effective marketing strategies to sustain their businesses. This study aims to examine the influence of marketing strategy, product suitability, consumer responsiveness, personal branding, and market demand on the existence of WFL Coffeeshop in Anambas Regency. A quantitative research approach was employed, using primary data collected through structured questionnaires distributed to WFL Coffeeshop consumers. The data were analyzed using statistical techniques to assess both partial and simultaneous effects among the research variables. The findings reveal that marketing strategy, product suitability, consumer responsiveness, personal branding, and market demand collectively influence the existence of WFL Coffeeshop. Each variable also demonstrates a significant effect, underscoring the importance of aligning products with consumer needs, responding effectively to customers, and building a consistent personal brand. This study concludes that an integrated marketing strategy is essential for maintaining business sustainability and competitiveness, particularly for coffee shops operating in emerging regional markets.